A közigazgatás szervezeti változásai a szabálysértési jog fórumrendszere tükrében - Árva, Zsuzsanna (Debreceni Jogi Műhely, 2014)
The paper introduces the most recent processes taking place within the Hungarian public administration from a special aspect and follows the system of the authorities of the misdemeanor law from the 19th century to nowadays. It presents the system of the monarchy, the councils and the period after the change of regime. The Constitutional Court with its Resolution no. 63/1997 (XII. 12.) declared the dual nature of offences – being against public administration and bagatelle cases pertaining to criminal law – and although with a different legal reasoning, it prescribed the right of access to court in both cases. The mentioned separation has resulted in conceptual problems exerting their influence to this day, at the same time the majority of authors dealing with this field instead of the majority opinion accepted the concurrent explanation of László Sólyom, to which Constitutional Court Judges János Németh and Tamás Lábady also joined. In 2012, however, several important changes took place simultaneously. The new Act on Offenses shifted towards criminal law while it terminated the right of local governments to regulate offenses. In parallel with this, the Act on Local Governments at the beginning provided an opportunity for the local governments to sanction anti-social behavior which was revoked by the Constitutional Court in the same year. The paper investigates the effect of the decisions of the Constitutional Court and analyzes the opportunities of public administration within the present legal framework to apply sanctions and defines those criteria on the basis of which the legislator could settle the current situation.